2011
DOI: 10.1029/2010ja016042
|View full text |Cite
|
Sign up to set email alerts
|

AKR modulation and global Pi2 oscillation

Abstract: [1] In this report we present a temporal relationship between ground Pi2 and auroral kilometric radiation (AKR). We analyzed six isolated substorm events, which were observed by the MAGDAS/CPMN ground magnetometer network and the plasma wave instrument onboard the Polar satellite. We found that the time derivative of the heightintegrated AKR power and the ground Pi2 D component had the same periodicity and that the two were synchronized with each other. When the D component fluctuated with the same (opposite)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
44
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(51 citation statements)
references
References 48 publications
(123 reference statements)
7
44
0
Order By: Relevance
“…In global high-correlation Pi 2 events, the high-to middle-latitude Pi 2 in the H (geomagnetically northward) and D (geomagnetically eastward) components contain waveforms that are highly correlated with low-latitude H Pi 2. Uozumi et al (2011) found that not only the high-latitude Pi 2 but also middle-and low-latitude Pi 2, which are highly correlated with lowlatitude H Pi 2, can be treated in the framework of global high-correlation Pi 2. Uozumi et al (2011) found that not only the high-latitude Pi 2 but also middle-and low-latitude Pi 2, which are highly correlated with lowlatitude H Pi 2, can be treated in the framework of global high-correlation Pi 2.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…In global high-correlation Pi 2 events, the high-to middle-latitude Pi 2 in the H (geomagnetically northward) and D (geomagnetically eastward) components contain waveforms that are highly correlated with low-latitude H Pi 2. Uozumi et al (2011) found that not only the high-latitude Pi 2 but also middle-and low-latitude Pi 2, which are highly correlated with lowlatitude H Pi 2, can be treated in the framework of global high-correlation Pi 2. Uozumi et al (2011) found that not only the high-latitude Pi 2 but also middle-and low-latitude Pi 2, which are highly correlated with lowlatitude H Pi 2, can be treated in the framework of global high-correlation Pi 2.…”
Section: Introductionmentioning
confidence: 98%
“…Uozumi et al (2009) found that the H component of a high-latitude Pi 2 exhibits systematic group delays (|T| <~100 s) from the low-latitude Pi 2 in H. On the other hand, the delay time of the high-latitude Pi 2 in the D component to the low-latitude Pi 2 from the H component was not significant (|T|<~10 s) in the entire nighttime sector, and the high-latitude D component Pi 2s switched their polarity around 1 hr MLT dawnward of the auroral breakup center that was identified by global auroral image of the Polar satellite. Uozumi et al (2009Uozumi et al ( , 2011Uozumi et al ( , 2016 proposed a generation and propagation mechanism of global high-correlation Pi 2 event based on ground observations. Uozumi et al (2009Uozumi et al ( , 2011Uozumi et al ( , 2016 proposed a generation and propagation mechanism of global high-correlation Pi 2 event based on ground observations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…During a width expansion, the intensity of the outgoing waves decreases. It is interesting to note that a similar correlation between the AKR power and low frequency oscillations of the magnetic field has been observed (Uozumi et al, 2011). For more detailed comparison with experimental data, it is also necessary to take into account the magnetic field and plasma inhomogeneities in the region of the AKR generation.…”
Section: Discussionmentioning
confidence: 99%